(untitled) (ENTHYMEMA, 2022)
This contribution, divided into two parts, aims to propose some reflections on the role of the ‘narrator’ in two comic adaptations of the famous short story The Sandman by E.T.A. Hoffmann. Following some theories on the subject, the first section investigates the narrative properties of this medium, specifically concentrating on the instance of the narrator. In the second part, the focus will be on the specific case of comic adaptations of narrative texts; specifically, through the analysis of the comics transposition of some passages of Hoffmann’s short story that are particularly interesting from a narratological point of view, some considerations will be presented on the role of the narrator and on its function within the two adaptations examined, in order to highlight the different expressive and narrative possibilities of comics.